Multi-Channel Configuration for improving received signal strength in non-line-of-sight environments of indoor visible light communication localization - Hilal A. Fadhil; Feras H. AlAttar; Tariq Adnan Fadil; Haider J. Abd (IAES Indonesian Section, 2022)
In modern engineering technologies, energy conservation is a factor of primary concern. A feature of Light-emitting diode (LED) light sources is the ability to transmit information in addition to illumination at no additional cost. VLC (Visible Light Communication) is gaining an upper hand over the traditional RF data communication model, as it utilizes a technology by which light can be used to transmit data. It is commonly seen that dealing with non-line of sight (NLOS) is a major challenge for VLC systems as the light intensity is reflected in a variety of directions. To overcome this drawback, a new technique based on multichannel configuration is utilized to enhance the overall system performance. An indoor VLC model is designed and simulated on the basis of the eye-diagram, bit error rate, and received power of the proposed model. We also investigated the model under the influence of ambient light noise. The corresponding results are compared with the conventional NLOS system and an inference made shows the significant improvement for the next-generation optical communication system.